Body mass index in relation to dental maturation of 10 to 14 years old school children in Erbil city. A cross-sectional prospective study - Omar Fawzi Chawshli; Yara Ismael Ameen (Erbil Dental Journal)
Background and Objectives: Estimation of dental age is based upon the rate of development and calcification of tooth buds and their progressive sequence of eruption in the oral cavity. The tooth calcification provides a valuable indicator of dental age and serves as an index of the maturation of the child. The aim of this study is to determine whether Body Mass Index (BMI) has association with dental maturation. Materials and Methods: A cross sectional study design was applied for the present study, 383 school children were participated in this study which nominated from Erbil city. For the sample to be representative the city was divided in to six geographic areas according to the municipalities, the samples randomly selected school children of 10 to 14 years old from both genders. The height and the weight of each participant had been recorded in the college of dentistry / Hawler Medical University in order to calculate the body mass index of the following the guidelines of centers of disease control (CDC), at the same time an orthopantomography radiograph had been used to investigate the stage of the dental maturation using the Demirjian method, finally, the relationship between BMI and dental maturation were investigated using chi square test with P value of ≤ 0.05 was considered significant difference. Result: there was a statistically significant relationship between dental maturation and BMI. The majority (93.6%) of samples with under-mature dentition were under-weight at the same time. The vast majority (96%) of samples with mature dentition had normal BMI. In the same manner, majority (91.7%) of samples with over mature dentition were over-weight too. Chi-square test was used to find out the association and P-value was 0.001 Conclusion: In conclusion, normal weight students have normal dental maturation, un-derweight students have under dental maturation and overweight or obese students have over dental maturation.